PERGESERAN BUDAYA SAPAAN DAN KEKERABATAN DI WILAYAH KECAMATAN KRATON YOGYAKARTA DAERAH ISTIMEWA YOGYAKARTA - SITI MUKMINATUN; Rahmi D Andayani; Erna Andriyanti (Jurnal Penelitian Humaniora, 2007)
This research entitled Pergeseran Budaya Sapaan dan Kekerabatan di Wilayah Kecamatan Kraton Yogyakarta Daerah Istimewa Yogyakarta “The shift of the address culture and kinship in the district of Yogyakarta Palace in Yogyakarta Special Territory” aims at describing the style of nominal address in the style of Javanese Language and Culture in Yogyakarta, the domain of kinship, the relationship between social status, age, social stratification toward the address forms and kinship, and the shift of address culture and kinship in the district of Yogyakarta Palace. This research is based on field survey and uses a descriptive qualitative method to describe the shift of the address culture and kinship from structural, semantic, and sociolinguistic perspective. The data are words and phrases related to the address forms and kinship which were collected from oral and written sources. The oral sources were taken through in-depth interviews with some informants around the district of Yogyakarta Palace while the written sources were from documents about address forms and kinship. The research instruments were the researchers themselves using validity test. The analysis was carried out through triangulation, peer checking and comparing with some related previous studies. The result shows that there are three kinds of nominal address; high, mid, and low style. Meanwhile, the kinship domains found in the district of Yogyakarta Palace are (1) sultanate, (2) aristocracy, (3) palace kinship, (4) familial relationship, (5) social status, (6) social stratification, (7) neighborhood, and (8) the degree of power in the palace. From this research it is found that social status, age, social stratification, sex influence the choice of nominal address. The shift of address forms and kinship includes (1) the shortening of nominal address, (2) the respect for the social stratification is considered, (3) the broadening of function, and (4) the low levels upgrade their address forms to have a social admiration.